EFFECT OF BAGASSE PARTICLE SIZE AND CORNSTARCH COMPOSITION ON BAGASSE BRIQUETTE PRODUCTION AS COOKING FUEL IN SUMBUL VILLAGE - Tiara Nur Azizah; Christyfani Sindhuwati (DISTILAT: Jurnal Teknologi Separasi, 2022)
Bagasse is one of the potential sources of biomass in Sumbul Village which is very abundant. This bagasse waste is accumulated on the side of the road which disturbs the aesthetics because it looks scattered and brings odor. The objective of this research was to make bagasse waste as briquettes for cooking fuel. This study used 2 variables, bagasse particle size (20, 40, and 60 mesh) and starch composition as an adhesive (10%, 20%, and 30% w/v). The parameters tested in this study were water content, ash content, calorific value, and ignition time. The results obtained were briquettes have a water content of 1.32% and ash content of 0.37%. Meanwhile, the best results were obtained on a variation of 60 mesh bagasse particles with 20% w/v corn starch composition which has a heating value of 3,215 J/g and an ignition time of 132 minutes.